Test and Analysis of the Mass Properties for the PRANDTL-D Aircraft - Callan, Kimberly (Proceedings of the Wisconsin Space Conference, 2012)
T he main objective of the "PRANDTL-D" project is to obtain the stability and control derivative yawing moment due to aileron deflection, CnÎ´a. The sign of CnÎ´a determines whether the "PRANDTL-D" aircraft experienced proverse or adverse yaw during flight. Proverse yaw, the desirable outcome, occurs when the aircraft yaws in the same direction as the turn due to a novel wing twist and bell-shaped lift distribution. Accurate moments of inertia are essential in order to create a dynamic model of the aircraft and compute the stability and control derivatives, including CnÎ´a. The robustness of the aircraft simulation also depends on the uncertainty of the mass properties. To obtain the moments of inertia, the aircraft will be hung from two filars and rotated in a bifilar pendulum test. A wireless inertial measurement unit will be used to capture the rotation rate data during testing. This data will be used in a bifilar pendulum simulation to analyze the data and obtain the experimental values. For the tests, our team used Pro Engineer to predict the moments of inertia, designed the test structure and specific testing procedures, and created a Simulink model of the bifilar pendulum test.Â